Comparison of methods for converting Dylos particle number concentrations to PM2.5 mass concentrations. (25th March 2019) - Franken, Remy; Maggos, Thomas; Stamatelopoulou, Asimina; Loh, Miranda; Kuijpers, Eelco; Bartzis, John; Steinle, Suzanne; Cherrie, John W.; Pronk, Anjoeka
Abstract: The aim of this study was to (a) develop a method for converting particle number concentrations (PNC) obtained by Dylos to PM2.5 mass concentrations, (b) compare this conversion with similar methods available in the literature, and (c) compare Dylos PM2.5 obtained using all available conversion methods with gravimetric samples. Data were collected in multiple residences in three European countries using the Dylos and an Aerodynamic Particle Sizer (APS, TSI) in the Netherlands or an optical particle counter (OPC, GRIMM) in Greece. Two statistical fitted curves were developed based on Dylos PNC and either an APS or an OPC particle mass concentrations (PMC). In addition, at the homes of 16 volunteers (UK and Netherlands), Dylos measurements were collected along with gravimetric samples. The Dylos PNC were transformed to PMC using all the fitted curves obtained during this study (and three found in the literature) and were compared with gravimetric samples. The method developed in the present study using an OPC showed the highest correlation (Pearson ( R ) = 0.63, Concordance ( ρ c ) = 0.61) with gravimetric data. The other methods resulted in an underestimation of PMC compared to gravimetric measurements ( R  = 0.65‐0.55, ρ c  = 0.51‐0.24). In conclusion, estimation of PM2.5 concentrations using the Dylos is acceptable for indicative purposes.